The Case for Christ A Journalist's Personal investigation of the Evidence for Jesus - Strobel, Lee (Grand Rapids Zondervan, 1998)
The book consists primarily of interviews between Strobel (a former legal editor at the Chicago Tribune) and biblical scholars such as Bruce Metzger. Each interview is based on a simple question, concerning historical evidence (for example, "Can the Biogr
Keywords: Jesus Christ -- Person and offices. Jesus Christ -- Historicity. Bible -- Evidences, authority, etc. Apologetics. Jesus Christ. Bible. Historicity of Jesus Christ. Authority -- Religious aspects. Christology